ENRICHING THE ENGLISH STUDENTS’ SPEAKING ABILITY BY APPLYING NARRATIVE STORY TELLING WITH GUIDED QUESTIONS - Jihad, Adriani (JOURNAL OF ADVANCED ENGLISH STUDIES, 2019)
Applying appropriate technique to expand the students speaking ability is the English lecturer’s responsibility in STKIP YPUP Makassar to create the situation. Narrative Storytelling with Guided Question is a technique in generating speaking class more enjoyable, fun and memorable for the students. This research aims at: (1) finding out whether or not narrative storytelling technique with guided questions enrich the students speaking ability and (2) knowing the students' attitude toward the use of narrative storytelling technique with guided questions in learning speaking.This research employed quasi experimental design. The population of this research was the students of English department at STKIP YPUP Makassar in academic year 2017/2018. The sample of this research consisted of 60 students that belong to two groups; 30 students in control group and 30 students in experimental group. The research data was collected by using speaking test through interview and questionnaire which were analyzed descriptively and by inferential statistic through SPSS 22.0 program. The students’ result of posttest of experimental group is significantly enrichd than the students’ result of posttest of control group by the mean score 71.45 > 59.74. The difference of both scores is statistically significant based on the t-test value at significant level 0.05 in which the probability value is lower than the significant level (0.00 < 0.05). The mean score of the students’ attitude is 79.10 and it is categorized as positive attitude. It can be concluded that narrative storytelling technique with guided questions is effective to enrich the students’ speaking ability, and the students give a positive attitude in learning speaking by applying narrative storytelling technique with guided questions.